Evaluasi Performa Sistem Informasi FMIPA Universitas Lampung Menggunakan Information Systems Functional Scorecard (ISFS) - Ilham Hardiyanto; Anie Rose Irawati; Yunda Heningtyas; Rico Andrian (Jurnal Pepadun, 2023)
The information system at FMIPA Unila (Faculty of Mathematics and Natural Sciences, University of Lampung) is intended to support both academic and non-academic activities within the FMIPA Unila community. However, the system frequently faces disruptions, ranging from server shutdowns to unauthorized access by malicious individuals. Furthermore, some of the information service menus and features are currently inaccessible within the FMIPA Unila information system. The main aim of this study is to evaluate the operational efficiency of the FMIPA Unila information system from the user's point of view. The research employs the Information Systems Functional Scorecard (ISFS) method, which comprises three assessment dimensions: system performance, information effectiveness, and service performance. To gauge system performance, questionnaires were distributed to 100 student participants who represent various departments at FMIPA Unila. According to the ISFS calculations, the overall performance of the Unila FMIPA information system can be generally deemed satisfactory. Recommendations for improving and fine-tuning the FMIPA UNILA information system include the provision and completion of information services currently missing from the Profile menu, Academic menu, Research and Service menu, Student Affairs menu, and Document menu. Furthermore, enhancements should be made to the system's menu navigation features and menu buttons to ensure their proper functionality.